Death of Languages and Endangered Languages in Costa Rica: The Exo-Community Perspective - Sánchez Avedaño, Carlos (2014)
In this article, we analyze three fundamental and recurrent interests in the out-group discourse (i.e., that of linguists, anthropologists, teachers and journalists), with regard to the phenomenon of language death and language endangerment in Costa Rica: document and describe languages before their imminent loss or due to academic reasons, describe language shift causes and processes, and claim for actions to maintain and revitalize languages.